Islamic Political Economy: Thought, Movement and Development - Devi Triana; Sholahuddin; Sajidah; Mashudi (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2025)
Islamic political economy is a discipline that studies the interaction between economic and political principles within the context of Islamic teachings. This article examines the evolution of Islamic political economic thought from the classical era to the contemporary era. This research also explores various Islamic economic movements that have emerged in response to global and regional economic challenges, including the emergence of the Islamic banking system and Sharia-based economic initiatives. Furthermore, this article evaluates recent developments in Islamic political economy, including the role of Islamic financial technology (Shariah Fintech), Sharia-based economic policies adopted by several countries, and global efforts to promote economic and social justice according to Islamic principles. With a comprehensive analysis, this article aims to provide in-depth insights into how Islamic political economy continues to develop and adapt in the face of rapidly changing global economic dynamics.